2022
DOI: 10.1111/odi.14168
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma ex pleomorphic adenoma of the submandibular gland: A retrospective analysis of 86 patients

Abstract: Objectives To evaluate the prognostic and locoregional metastatic features of carcinoma ex pleomorphic adenoma of submandibular gland (SMG‐CXPA) and improve the understanding of this uncommon condition. Patients and methods We retrospectively reviewed patients who were diagnosed with SMG‐CXPA. The survival data of SMG‐CXPA patients were statistically analyzed using Cox regression and Kaplan–Meier method. The associations between cervical metastasis and clinicopathological parameters were evaluated using chi‐sq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…A few of patients with MSLGT pathological types are at some risk of cervical nodal metastasis, with a documented metastasis rate of up to 60% for non‐ACC malignant sublingual gland tumors (Park, Cho, et al, 2021). However, ACC is more frequent among sublingual gland malignancies therefore, cervical nodal metastasis of MSLGT is not that common when compared with other major salivary gland malignancies (Liu, Lu, et al, 2022; Lombardi et al, 2017). Instead, there is some possibility of distant metastasis for MSLGT, of which 70% were pulmonary metastasis (Spiro et al, 1974).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few of patients with MSLGT pathological types are at some risk of cervical nodal metastasis, with a documented metastasis rate of up to 60% for non‐ACC malignant sublingual gland tumors (Park, Cho, et al, 2021). However, ACC is more frequent among sublingual gland malignancies therefore, cervical nodal metastasis of MSLGT is not that common when compared with other major salivary gland malignancies (Liu, Lu, et al, 2022; Lombardi et al, 2017). Instead, there is some possibility of distant metastasis for MSLGT, of which 70% were pulmonary metastasis (Spiro et al, 1974).…”
Section: Introductionmentioning
confidence: 99%
“…Malignant tumors of the salivary glands are rare and account for <5% of head and neck cancer, with most malignant tumors originating from the parotid and submandibular glands (Geiger et al, 2021; Liu, Lu, et al, 2022; Liu, Xu, et al, 2022). According to a large‐scale analysis, malignant sublingual gland tumors (MSLGT) are even rarer, constituting only 0.3%–1% of salivary gland tumors and about 1.2% of salivary gland malignancies (Eveson & Cawson, 1985; Lee et al, 2016; Tian et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The benign tumors found in SMG mainly include pleomorphic adenoma, myoepithelioma, and basal cell adenoma, while malignancies of SMG mainly consist of adenoid cystic carcinoma (AdCC), carcinoma ex‐ pleomorphic adenoma (CXPA), and mucoepidermoid carcinoma (MEC). Our previous study retrospectively reviewed 86 cases of patients diagnosed with CXPA of SMG (SMG‐CXPA) and concluded that SMG‐CXPA is a high‐grade malignancy with an unfavorable prognosis (Liu et al, 2022). Elective neck dissection should be performed in SMG‐CXPA patients, which could illicit risk of locoregional metastasis (including sex, tumor size, clinical tumor stage, clinical lymph node stage, histological grade, invasiveness, malignant components, perineural invasion).…”
Section: Introductionmentioning
confidence: 99%